1975
DOI: 10.1042/bj1460497
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of pulmonary antiotensin-converting enzyme (kininase II)

Abstract: Goat antibodies to pig lung angiotensin-converting enzyme (kininase II) were conjugated to microperoxidase. Rat lung tissue, previously incubated with non-immune goat serum, was incubated with the antibody-microperoxidase conjugate and then with H2O2 and 3,3-diaminobenzidine. Electron microscopy revealed reaction product on the plasma membrane and caveolae of endothelial cells, especially those of capillaries and venules. These results support the hypothesis that angiotensin I and bradykinin are metabolized by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
1
5

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(99 citation statements)
references
References 9 publications
(13 reference statements)
4
87
1
5
Order By: Relevance
“…Two probable markers are available for the alveolar endothelial cells; physiological evidence suggests that membrane-bound carbonic anhydrase is concentrated in endothelial cells (Klocke, 1978;Crandall & O'Brasky, 1978;Effros et al, 1978) and angiotensin converting enzyme is situated along the luminal surface of pulmonary endothelial cells (Ryan et al, 1975). Morphometric data on the developing rat lung have been published .…”
Section: Discussionmentioning
confidence: 99%
“…Two probable markers are available for the alveolar endothelial cells; physiological evidence suggests that membrane-bound carbonic anhydrase is concentrated in endothelial cells (Klocke, 1978;Crandall & O'Brasky, 1978;Effros et al, 1978) and angiotensin converting enzyme is situated along the luminal surface of pulmonary endothelial cells (Ryan et al, 1975). Morphometric data on the developing rat lung have been published .…”
Section: Discussionmentioning
confidence: 99%
“…To establish a connection with previous electron microscopic immunocytochemical findings, we used several antibodies directed against integral membrane proteins known to be expressed at the level of endothelium in lung and/or other organs, e.g., thrombomodulin (Horvat and Palade, 1993), functional thrombin receptor (Horvat and Palade, 1995), podocalyxin (Horvat et al, 1986), and the angiotensin-converting enzyme (ACE;Ryan et al, 1975). Figure 6A shows the results obtained and compares the distribution of these antigens with that of caveolin.…”
Section: Presence Of Endothelial-specific Markersmentioning
confidence: 99%
“…Histochemical studies with antibody prepared against pure enzyme established that the protein was a constituent of the luminal surface of pulmonary vascular endothelial cells (8), and subsequent investigations (9) revealed that the enzyme was also a specific vascular endothelial component in other organs.…”
Section: Discussionmentioning
confidence: 99%
“…It also liberates Phe-Arg and Ser-Pro from bradykinin (4, 5), thereby inactivating this vasodepressor nonapeptide. The enzyme is a glycoprotein (5, 6) that is localized on the luminal surface of vascular endothelial cells in anatomic juxtaposition to the circulation (7)(8)(9). Specific chemical inhibitors of its activity (10-12) can reverse experimental renovascular hypertension (13-17) and can reduce blood pressure in a substantial fraction of human hypertensive disease (18, 19).…”
mentioning
confidence: 99%